How does the government create 8% growth? A critical transitivity analysis of economic rhetoric in Indonesia - Wida Mulyanti; Adi Hidayat; Mahardhika Zifana (Universitas Islam Negeri Ar-Raniry, 2026)
This study employs Fairclough's Critical Discourse Analysis (CDA) framework, integrated with Halliday's transitivity system from Systemic Functional Linguistics (SFL), to examine the economic discourse produced by Indonesia's Minister of Finance. The analytical method operationalizes Fairclough's three-dimensional model—textual analysis, discourse practice, and sociocultural practice—through the systematic application of the SFL transitivity system as its principal grammatical tool. At the textual level, transitivity analysis maps the ideational function of language by classifying 768 clauses into six process types: material (31.0%), relational (27.1%), mental (19.1%), verbal (8.7%), existential (2.3%), and behavioral (2.0%), with the remainder comprising minor and elliptical clauses. An in-depth analysis of the three dominant process types reveals distinct ideological functions. Material processes construct the state as the primary economic actor capable of generating growth through deliberate intervention. Relational processes naturalize economic challenges as objective conditions necessitating state response, rather than as outcomes of contestable policy decisions. Mental processes assert epistemic authority while simultaneously constructing a form of epistemic nationalism that challenges the legitimacy of international financial institutions. By fully integrating Fairclough's three-dimensional framework with focused transitivity analysis, this study demonstrates how economic discourse during Indonesia's governmental transition encodes a developmental state ideology, naturalizes active state intervention, and asserts postcolonial epistemic sovereignty. The findings advance CDA methodology by providing a replicable model for the integrated linguistic analysis of economic policy discourse in transitional political contexts.